2020
DOI: 10.1177/1367006920947180
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring allophonic structure and phonetic detail in a bilingual community: The production of laterals by Sylheti-English bilingual children

Abstract: Aims and objectives: In this study, we consider the acquisition of allophonic contrast and phonetic detail in lateral consonants by second-generation Sylheti-English bilingual children in London, UK. Design/methodology/approach: Acoustic analysis was conducted on productions of /l/ by Sylheti bilingual children, Sylheti monolingual adults and English monolingual children. Data and analysis: Tokens of /l/ were elicited across initial, medial and final word positions from 14 bilingual Sylheti-English children, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…Furthermore, in their Sylheti, bilinguals who were born in the UK were not significantly different from the late or early arrivals, but they were significantly different from the Sylheti monolinguals, displaying a production trend toward English. To some extent, these findings align with segmental research in similar communities that has shown that second-generation speakers often exhibit non-native features in the heritage language (Kupisch et al, 2014;Mayr & Siddika, 2016;McCarthy et al, 2013McCarthy et al, , 2014McCarthy et al, , 2011; but see Kirkham & McCarthy, 2020). This pattern might have been driven by their Sylheti language use patterns.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, in their Sylheti, bilinguals who were born in the UK were not significantly different from the late or early arrivals, but they were significantly different from the Sylheti monolinguals, displaying a production trend toward English. To some extent, these findings align with segmental research in similar communities that has shown that second-generation speakers often exhibit non-native features in the heritage language (Kupisch et al, 2014;Mayr & Siddika, 2016;McCarthy et al, 2013McCarthy et al, , 2014McCarthy et al, , 2011; but see Kirkham & McCarthy, 2020). This pattern might have been driven by their Sylheti language use patterns.…”
Section: Discussionsupporting
confidence: 83%
“…In comparison, those who arrive as children or second-generation bilinguals typically display incremental changes toward the majority language production patterns in their native language (Evans et al, 2007;Mayr & Siddika, 2016;McCarthy et al, 2013McCarthy et al, , 2011Nagy & Kocketov, 2013;Sharma & Sankaran, 2011; but see Kirkham & McCarthy, 2020). For example, Nagy and Kotchetov (2013) showed an intergenerational trend toward the English VOT pattern in Russian and Ukrainian heritage language speakers in Toronto, and Mayr and Siddika (2016) found incremental changes in VOT patterns across generations of Sylheti heritage language speakers in Wales, UK.…”
Section: Previous Research On Speech In Heritage Language Communitiesmentioning
confidence: 99%
“…These findings were confirmed by , who studied how an Indonesian-German bilingual child could comprehend two languages. The findings indicated that adults' verbal inputs in the form of words spoken to the child were brief utterances, which often included high-pitched sounds and many repetitions of the same sounds (Georgiou, 2019;Kempe et al, 2019;Kirkham & McCarthy, 2021). The child could comprehend terms in both Indonesian and German throughout the preproduction stage, including some bilingual synonyms.…”
Section: Findings and Discussion Canonical Babbling And Comprehension...mentioning
confidence: 97%
“…Acoustic emission is a type of elastic wave, and in the real environment, it can be divided into transverse waves, longitudinal waves, and surface waves, depending on how the sound waves propagate in the medium and the direction of vibration. When propagating in solids, it causes local deformation of the medium, and two types of waves appear simultaneously: longitudinal (compressional) and shear (transverse) waves, which have different speeds and are automatically separated after leaving the source [16]. When the acoustic signal propagates to the junction of air and solid media, the acoustic wave is reflected and refracted, which causes it to undergo a waveform transition, followed by the simultaneous appearance of two waveforms.…”
Section: Multimodal Intelligent Acoustic Sensor Sound Acquisitionmentioning
confidence: 99%